WAYS TO WORK ON THE PIANO IN EXTRACURRICULAR ACTIVITIES - p.f.f.d.Pardayev Sobit Abdivali o‘g‘li; Kadirova Shahzoda Shatlik qizi (Web of Journals Publishing, 2024)
This article covers the methods of working on the piano instrument in extracurricular activities, it contains information about the history of the creation of the piano instrument and how it has been preserved to this day.
Keywords: Types of training, piano, art, renaissance period, music, culture, grand piano, musical-aesthetic, education-music, pedagogy, performance skills.